2017
DOI: 10.1051/epjconf/201713707011
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of dense two-color QCD within lattice simulations

Abstract: Abstract. We present the results of a low-temperature scan of the phase diagram of dense two-color QCD with N f = 2 quarks. The study is conducted using lattice simulation with rooted staggered quarks. At small chemical potential we observe the hadronic phase, where the theory is in a confining state, chiral symmetry is broken, the baryon density is zero and there is no diquark condensate. At the critical point µ = m π /2 we observe the expected second order transition to Bose-Einstein condensation of scalar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They call such a new phase of matter the "quarkyonic matter" which reflects the coexistence of quarks and baryons: the thermodynamic properties of the system are dominated by quark Fermi seas but the elementary fermionic excitations are confined baryons near the Fermi surfaces. Interestingly, recent LQCD simulation showed that even at N c = 2, the notion of quarkyonic matter is serviceable [14]. In this case, the LQCD found that the deconfinement never happens at zero temperature when µ B increases; instead, the system at large µ B is characterized by quarks always residing in Fermi seas and diquark condensate near the Fermi surface.…”
Section: Introductionmentioning
confidence: 99%
“…They call such a new phase of matter the "quarkyonic matter" which reflects the coexistence of quarks and baryons: the thermodynamic properties of the system are dominated by quark Fermi seas but the elementary fermionic excitations are confined baryons near the Fermi surfaces. Interestingly, recent LQCD simulation showed that even at N c = 2, the notion of quarkyonic matter is serviceable [14]. In this case, the LQCD found that the deconfinement never happens at zero temperature when µ B increases; instead, the system at large µ B is characterized by quarks always residing in Fermi seas and diquark condensate near the Fermi surface.…”
Section: Introductionmentioning
confidence: 99%
“…To study the phase diagram of QC 2 D with N f = 2 flavors we used a 16 3 × 32 lattice, simulating with β = 2.15, ma = 0.005, the lattice spacing a = 0.112(1) fm and the pion mass M π = 378(4) MeV (detailed description of the action and parameters may be found in [24]). …”
Section: The Lattice Set-upmentioning
confidence: 99%
“…Also in N = 1 SUSY 1+3 QCD with N f = N c + 1, while confinement is realized, chiral symmetry breaking does not occur. A recent lattice study of SU(2)-color QCD with N f = 2 shows that a confined but chiral-restored phase is realized at a large baryon density [11]. Figure 1.…”
Section: Introductionmentioning
confidence: 95%